Treponema denticola Induces Alzheimer-Like Tau Hyperphosphorylation by Activating Hippocampal Neuroinflammation in Mice. (July 2022) - Tang, Z.; Cheng, X.; Su, X.; Wu, L.; Cai, Q.; Wu, H.
Alzheimer's disease (AD) is the most common type of dementia. Tau hyperphosphorylation and amyloid β (Aβ) deposition are the key pathological hallmarks of AD. Recent studies have shown that periodontitis is a significant risk factor for AD. The periodontal pathogen Porphyromonas gingivalis and its virulence factors have been shown to initiate and promote the hallmark pathologies and behavioral symptoms of AD. A possible link between Treponema denticola, another main periodontal pathogen, and AD has been reported. However, the role of T. denticola in AD pathogenesis is still unclear, and whether T. denticola and P. gingivalis exert a synergistic effect to promote AD development needs to be further studied. In this study, we investigated whether oral infection with T. denticola caused tau hyperphosphorylation in the hippocampi of mice and explored the underlying mechanisms. Orally administered T. denticola induced alveolar bone resorption, colonized brain tissues, and increased the activity of the phosphokinase GSK3β by activating neuroinflammation in the hippocampus, thus promoting the hyperphosphorylation of the tau protein at Ser396, Thr181, and Thr231 in mice. An in vitro study with BV2 and N2a cell models of T. denticola invasion also verified the role of this pathogen in tau phosphorylation. T. denticola and P. gingivalis were not found to exert a synergistic effect on tau phosphorylation. In summary, these findings provide new insight into the important role of T. denticola in AD pathogenesis, providing biological connections between periodontal diseases and AD.